NILAI PENDIDIKAN KARAKTER DALAM FILM KARTUN SPONGEBOB SQUAREPANTS: SPONGE ON THE RUN FULL MOVIE PADA YOUTUBE - Besse Febriani; Sumiharti Sumiharti; Sainil Amral (Universitas Batanghari, 2025)
This research describes the value of character education contained in the cartoon film Spongebob Squarepants: Sponge on The Run Full Movie on YouTube. Apart from that, this research aims to complete the final assignment in the Indonesian Language and Literature Education study program, Department of Language and Arts Education, Faculty of Teacher Training and Education, Batanghari University, Jambi. This research is in the form of qualitative descriptive research. Descriptive research is to describe the research objectives. The qualitative approach is used as a technique to describe data analysis not in the form of numbers but in the form of words. The results of this research illustrate the value of character education which consists of 5 aspects. The value aspect of character education is honesty, 32 quotation data were found, 12 quotation data were found to be friendly, 5 quotation data were found for love of peace, 4 quotation data were found for social care and 6 quotation data were found for responsibility. From the results of this research, it was found that the most dominant data was honest attitude. Honesty is a character education value that must be inherent in humans.